Blockchain-based Health Monitoring System; Functioning with IoT and WBAN’s - Adarsh T. K, K. P. Vjayakumar (International Journal of Advanced Science and Technology, 2020)
Wearable medical devices and wireless body area networks with sensors continuously generate a large amount of data. Due to the increasing usage of health monitoring system in IoT, the patient with the habitual disease are easily curable at the early stages . A WBAN helps to monitor the health of a patient without any inhabitation of their normal life. The development of technology improves the popularity and efficiency of traditional hospital systems, especially in remote places. However to provide secure and efficient health care systems, a Blockchain-based health care monitoring system with Internet of Things and wireless body area networks(WBAN) is introduced. In this proposed work, the Blockchain technology is utilized as data transmitting and storage to meet the secure environment and traditional wireless body area network and internet of things technology use for monitoring as well as collecting medical health data. The proposed system has the advantages of utilizing low system requirements and provide high security for medical data